Pemberian suplemen seng sulfat dan pengaruhnya terhadap kadar seng serum dan jumlah CD4+ pada wanita usia lanjut sehat - Yang Rusfinda Sari; Muhammad Juffrie; I Dewa Putu Pramantara (Jurnal Gizi Klinik Indonesia, 2009)
Background: Aging is a natural process which happens to all living creatures. Aging is followed by declining physiological function. Elderly is a risk factor of micronutrient deficiency including zinc which has an important role in the immune system. This condition causes declining cellular immunity functions through reduced amount of CD4 .Objective: To identify the effect of zinc sulphate supply to serum zinc level and amount of CD4  among the elderly.Method: The study used clinical test research design, one group pre-post test design (before and after trial). Subject of the study were “healthy” elderly individuals of more than 60 years old, willing to be studied. Assessment on nutritional status, physical examination and zinc level were made to the subjects. Next, subjects were supplied with 15 mg of zinc supplement once a day for 28 days. Then, re-examination was made to identify zinc level and the amount of CD4  lymphocyte. Statistical analysis used paired t-test.Results: Average age of the elderly observed (n = 30) was 64.43 ± 3.10 years. Average zinc level before the study was 5.85 ± 1.95 μmol/L, as many as 26 subjects (86%) had zinc under normal level, 4 subjects (14%) had normal zinc level + + + and no subject had zinc above normal level. Zinc level at the end of the study increased in as many as 27 subjects (90%) with average as 4.54 ± 3.84 μmol/L (p < 0.001). The amount of CD4  lymphocyte increased in 11 subjects (36%) with + average increase 26.83 ± 137.46 (/mm) (p = 0.29). Factors affecting increase of CD4 lymphocyte were age, weight, score of mini nutritional assessment and upper arm circle, and preliminary zinc level.Conclusion: The supply of 15 mg zinc for 28 days among the elderly could elevate serum zinc level significantly and could increase the amount of CD4  lymphocyte only in 11 subjects (36%).